Identifying home advantage in international tennis and golf tournaments - Nevill, A. M.; Holder, R. L.; Bardsley, A.; Calvert, H.; Jones, S. (Journal of Sports Sciences, 1997)
A regression analysis of competitors' tournament results in relation to their world rankings was proposed to identify the effect of home advantage in international 'grand-slam' tennis and 'major' golf tournaments. The results provided little evidence of home advantage in either the grand-slam tennis or the golf tournaments held in 1993. The only possible evidence of home advantage was found in the Wimbledon tennis and the US Open golf championships. Even these findings can be explained, at least partially, by (1) the availability of information concerning the low world rankings of the British tennis players competing at Wimbledon, and (2) selective entry, allowing only the world's top-ranked foreign golfers into the US open golf tournament. In both cases, the lower ranking home competitors have a greater opportunity to perform above their anticipated world rankings. Therefore, provided entry into tennis and golf tournaments is truly 'open' to both the host nation's representatives and foreign competitors alike, home advantage does not appear to be a major factor influencing the competitors' performance in such competitions. These findings may be explained by the relatively objective nature of the scoring systems used in tennis and golf, unlike the subjective influence of refereeing decisions on the results of team-games such as soccer.